Long-Range Planning in North American Unions : Preliminary Findings - Reshef, Yonatan; Stratton-Devine, Kay (Relations industrielles / Industrial Relations, 1993)
The content of union planning, as well as union leader perceptions Of the effectiveness and extent of implementation of their plans are explored in this research. Data were gathered from a survey of all national and international unions in North America. Results indicate that 24.4 per cent ofthe respondent unions engage in long-range planning, with education, budgeting and political action being the most frequently cited topics.